Harmful Algal Blooms and Wind-related Variables Association - Xanthopoulou, Georgia; Kechagias, Dionysios; Koukaras, Konstantinos; Aligizaki, Katerina; Bratsas, Charalampos (European Journal of Sustainable Development, 2025)
Harmful algal blooms (HABs) are rapidly expanding in marine environments, posing serious risks to ecosystems, public health, and water quality. There is a growing need for more accurate forecasting techniques and intelligent systems that can generate accurate forecasts about the presence of HABs and, as a result, evaluate the effects of them on water quality. Direct forecasts of HABs presence are extremely difficult to be implemented due to the nature of the problem. Many studies use chlorophyll concentrations to detect HABs but such an alteration in chlorophyll concentration consists an immediate effect and not the root of the problem. Trying to early detect a forthcoming HAB, by investigating the impact of wind-related variables in the appearance of a HAB event in the marine system of Thermaikos gulf (NW Aegean Sea) with in-situ data, is the purpose of this research. Primary results have shown a causation among them, especially to east and north-west winds, leading to research paths towards to the spatial distribution of the phenomenon. An outcome that demonstrates the potential transporting of the HAB and also could assist in the creation of early warning systems. Keywords: HABs, wind, causal inference, prediction, early warning